Case Report: Relapsing pleural effusions and coated aorta revealing Erdheim–Chester disease - Ouattara, Tiépé Rokia; Pezel, Théo; Lorillon, Gwenael; Kante, Aïcha; Reiner, Peggy; Le Gal, Aurélie; Lefèvre, Marine; Vieira, Thibault; Mouly, Stéphane; Tazi, Abdellatif; Haroche, Julien; Goncalves, Trecy; et al. (Frontiers in Immunology, 2025)
Erdheim–Chester disease (ECD) is a rare histiocytic disorder with localized presentations or multisystem disease. Clinical presentations of ECD are usually non-specific and depends on the site of involvement. ECD can involve one or several organs. Clinical manifestations range from asymptomatic lesions to severe and life-threatening organ dysfunction. Hence, accurate and timely diagnosis is challenging given the rarity and varied presentation of ECD. The most common clinical manifestations are bone pain related to osteosclerosis, usually in the lower limbs. We report here a case with no obvious clinical manifestation of ECD preceding initial recurrent pleural effusions. The diagnosis of ECD was suggested based on pleural thickening revealed by relapsing pleural effusions combined with radiological finding of a coated aorta and slight perirenal infiltrate. Pleural biopsy revealed collagen fibrosis, and immunohistochemistry with the anti-CD163 antibody showed an important infiltration by histiocytes, strong cytoplasmic phosphorylated ERK in the lesional cells, and positive factor XIIIa staining. A cell-free DNA from peripheral blood revealed negative BRAF mutation and the presence of MAP2K1 mutation, a key driver mutation in ECD. The diagnosis is often suggested based on clinic-radiological presentation but requiring histopathology to establish a final diagnosis of ECD. Plasma cell-free DNA is a promising and non-invasive tool to detect key driver mutations.